2021
DOI: 10.12956/tchd.755871
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Öğrencilerinde Obezite İnsidansının Saptanması; 4 Yıllık Kohort Çalışmasının Ön Bulguları

Abstract: Bu çalışmada, ilkokul öğrencilerinde obezite insidansının belirlenmesi amaçlanmıştır.Gereç ve Yöntemler: Kohort türündeki bu çalışma, Konya ili Meram ilçesinde yer alan ikisi özel, ikisi devlet okulu olmak üzere dört ilk öğretim okulunda yürütüldü. Çalışmanın örneklem büyüklüğü 181 olarak hesaplandı. Çalışmanın ilk verileri 29 Nisan -07 Mayıs 2019 tarihleri arasında toplandı. Araştırma için, çalışmacılar tarafından 45 sorudan oluşan bir veri toplama formu geliştirildi. Velileri tarafından araştırmaya katılmala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the literature, it has been reported that parental education level and occupation had direct influence on obesity status of children. 17 Again, in previous studies, it was found that parental education level has influence on healthy lifestyle in adolescents. [18][19][20] In a study on elementary school students, it was reported that obesity rate was significantly higher in children of working mothers while majority of children (70.4%) of housewives were non-obese.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, it has been reported that parental education level and occupation had direct influence on obesity status of children. 17 Again, in previous studies, it was found that parental education level has influence on healthy lifestyle in adolescents. [18][19][20] In a study on elementary school students, it was reported that obesity rate was significantly higher in children of working mothers while majority of children (70.4%) of housewives were non-obese.…”
Section: Discussionmentioning
confidence: 95%
“…When the effect sizes between genders were analyzed, it was observed that the lowest effect size was in body weight and the highest effect size was in the physical activity sub-dimension of the obesity awareness scale. In the study conducted by Uyar et al 34 it was determined that the majority of students with underweight or normal weight were in public schools, while overweight and obese students were private school students. It was determined that students in the underweight and normal categories had high rates of taking nutrition to school, while overweight and obese students were more likely to eat from the school canteen and take nutrition with them.…”
Section: Discussionmentioning
confidence: 99%